The effects of social media on interpersonal communication among university students in Klang Valley - Ong, Shu Wen (2023)
Social media has emerged as a powerful tool for communication, empowering individuals to express themselves effectively and connect with like-minded people across the globe. However, despite its benefits, social media is causing people to spend more time in the virtual world at the expense of traditional social interactions in the real world. Thus, this research aims to explore the effects of social media on interpersonal communication among university students in Klang Valley. 107 sets of questionnaires were distributed via Google Form and the collected data was analysed by Statistical Package for Social Science version 29 (SPSS). The findings of this research show that university students have a strong attachment to social media. They remained positive towards social media usage and agreed that social media helps them to enhance their interpersonal communication as well as improve relationships.